The Effect Of Earning Persistence and CSR Disclosure On Earning Response Coefficient with Profitability as A Moderating Variabel - Oktavia, Ayu Citra Lestari; Wijaya, Herman (STIE Tri Bhakti, 2025)
This study aims to examine and analyze the influence of earnings persistence and corporate social responsibility (CSR) disclosure on the earnings response coefficient (ERC), with profitability as a moderating variable. This quantitative research uses secondary data obtained from annual reports and sustainability reports. The sampling technique used is purposive sampling, resulting in 35 companies with a total of 175 observations. The data analysis method employed is panel data regression and moderated regression analysis using EViews 12 software. The results show that earnings persistence does not significantly affect ERC, CSRD has a significant effect on ERC, and profitability strengthens the effect of both earnings persistence and CSRD on ERC.